The research focus and development trend of art therapy in Chinese education since the 21st century - Cui, Yingying; Wang, Fenping (Frontiers in Psychology, 2022)
Since the 21st century, art therapy has made great progress and development in China’s education. To find out the relationship between art therapy and special children, hundreds of related literatures were analyzed using co-word analysis software, which shows that art therapy is increasingly important in special children and their education. Expressive art therapy has a good development prospect in college students’ mental health education and group counseling. The connotation of group painting therapy is constantly enriched. The theme research of mandala painting therapy is closely related, and painting art therapy focuses on the psychological counseling research of different groups, but the two are still in the marginal position in the whole research, and have not been paid attention to. Therefore, in the future research, firstly, we should continue to strengthen the research of art therapy and expressive art therapy in special education and individual mental health education; second, further broaden the depth and breadth of group painting therapy; third, strengthen the study of mandala painting therapy and painting art therapy.